Design and Optimization of an Uneven Wave-like Protrusion Channel in the Proton Exchange Membrane Electrolysis Cell Based on the Taguchi Design - Zhong-Liang Feng; Tian-Jun Zhou; Shen Xu; Guo-Liang Wang; Lu-Haibo Zhao; Bo Huang (Energies)
The design of channel geometry plays a critical role in the performance of proton exchange membrane electrolytic cells (PEMECs), particularly in addressing challenges such as bubble accumulation and pressure drop, which hinder efficient hydrogen production. This study introduces an innovative uneven wave-like protrusion channel structure for PEMECs, designed to optimize mass transfer and bubble removal while minimizing energy losses. A combination of three-dimensional numerical simulations and the Taguchi design method is employed to systematically investigate the impact of protrusion height, width, and spacing on key performance metrics, including pressure drop, oxygen output, and volumetric gas content. The effects of different water supply flow rates and temperatures on the electrolytic cell were also investigated through visualization experiments. The results show that the channel with inhomogeneous waveform protrusions has superior PEMEC performance compared with the conventional single serpentine channel. In addition, the waveforms of the waveform protrusions were optimized using the Taguchi design method. The results obtained further optimized the PEMEC performance by increasing the outlet oxygen volume by 8.97%, reducing the average pressure drop by 4.4%, and decreasing the volumetric gas content by 20.26%.